Peningkatan Ekonomi Masyarakat Kecamatan Cigugur, Kuningan, Jawa Barat - Marwasta, Djaka; Catur Ari Firmansyah (Direktorat Pengabdian kepada Masyarakat, 2023)
Student Community Services are an event for lecturers, and students as well, to share knowledge and learning the experience with the community as an implementation of one of the Three Pillars of Higher Education. In practice, lecturers and students are required to adapt to new environments, understand different social dynamics, and learn to encourage and empower communities in a such kind of structured time and mechanism. This activity aims to (1) educate students to understand and trying to solve the problems that faced by the community in an interdisciplinary scientific manner, and (2) provide knowledge about local resource-based tourism village planning in Cigugur community. The method used is participatory learning by applying the pentahelix model concept. As an activity with the pentahelix concept, this activity involves academics (students and lecturers), bureaucracy (village, sub-district and district governments), business (Village-Owned Enterprises and Small and Medium Enterprises), the community, and the media. Collaboratively, all of these stakeholders actively participate in efforts to realize Cisantana Village as a tourist village by prioritizing local resources and wisdom. The main result of this activity is that lecturers and students as agents of change are able to deliver the knowledge they have, as well as the community and village government officials to gain increased literacy and understanding of tourism village development planning as a lever for the community’s economy. Based on the results of this activity it can be concluded that this activity provides benefits simultaneously, both for lecturers and students as well as for the community and village officials in terms of the ability to understand and implement the concept of planning a tourism village based on local resources. This activity also has a high potential for sustainability because the community can gain the benefit from it as a lever for the economy of the village community.